Bullying in Higher Education from a Human Rights Perspective: Pembullyan Di Perguruan Tinggi Dalam Perspektif HAM - Haikal Pratama; Junaidi Juliandi (Indonesian Journal of Law and Economics Review, 2026)
General Background Bullying in higher education represents a complex phenomenon affecting students’ psychological, social, and academic conditions while challenging the protection of human dignity within a human rights framework. Specific Background Various legal instruments and institutional regulations exist to address violence in academic environments, yet bullying continues to occur in verbal, physical, psychological, and digital forms. Knowledge Gap The absence of a specific legal classification of bullying creates fragmented interpretation within criminal law and reveals a discrepancy between normative provisions and actual enforcement. Aims This study aims to examine bullying in higher education from a human rights perspective and evaluate existing legal policies in addressing such cases. Results The findings show that bullying constitutes a violation of fundamental rights, particularly the right to security and dignity, while legal protection remains weak due to low human rights awareness, ineffective reporting systems, strong seniority culture, and unequal power relations. Existing regulations rely on general criminal provisions, resulting in inconsistent handling and limited victim protection. Novelty This study emphasizes structural weaknesses in current legal arrangements and highlights the need for a comprehensive legal framework grounded in human rights principles. Implications Strengthening human rights-based policies, integrating character education, and establishing effective protection systems are necessary to create a safe and equitable academic environment. Highlights• Bullying categorized through general criminal provisions without specific legal definition• Victim safeguards constrained by weak reporting systems and dominant power structures• Human rights violations linked to security and dignity within academic environments KeywordsBullying; Human Rights; Legal Policy; Higher Education; Victim Protection